PENINGKATAN KESEJAHTERAAN PETANI MELALUI PENGENALAN SISTEM PERTANIAN TERINTEGRASI BUDIDAYA KELAPA, CABAI MERAH, DAN LELE KOLAM TERPAL - Ulhaq, Riza; Weihan, Rayhan Amadius; Nasution, Anisah (Universitas Mataram, 2024)
Simeulue district in Aceh has great potential in coconut production, but farmers in Bubuhan village face several challenges in increasing their productivity and income. The challenges faced by the Karanjaya Farmer Group can be addressed by adopting an integrated farming system, which combines coconut with other crops and aquaculture to increase productivity and sustainability. The adoption of this system is expected to not only increase yields, but also provide additional income and economic security for the farmers. The purpose of this activity is to provide knowledge and skills to members of the Karanjaya Farmer Group regarding optimal land management through commodity diversification so that farmers are able to improve their welfare. The community service activity in Bubuhan Village on 5 October 2024 aimed to empower the Karanjaya Farmer Group through the introduction of an integrated farming system. The participants were given leaflets, attended a pre-test, presentation, interactive discussion, and post-test to ensure in-depth understanding. Based on the results of the post-test and pretest of 14 participants, it can be seen that there is a change in the increase in farmers' knowledge of integrated farming systems between coconut, chilli and catfish cultivation in tarpaulin ponds with the expected answers of 92%. The results of the service are expected to improve the welfare of farmers in a sustainable manner through the application of integrated agriculture